Nanopharmaceutics - Ali, Javed (International Journal of Pharmaceutical Investigation)
Nanotechnology is now a part of our everyday life with or without our knowledge. Then, why can pharmaceutics not conceive this technology for its betterment? Yes, the same has been done for many years in the past in pharmaceutics and now nanopharmaceutics can be considered as one of the subdivisions of pharmaceutics. Although the term “nanopharmaceutics” is not being started to be used widely, I feel that it would be more suitable when we discuss the application of nanotechnology to drug delivery systems. “Nanopharmaceutics” can be defined as the science that deals with the application of the principles of nanotechnology in pharmaceutics. These delivery systems, because of their size effect, are capable of altering the properties of a drug, including their bioavailability, biodistribution and pharmacokinetics. Nanosizing of the drug itself is also another well-accepted and established technique for altering its properties.